Abdominal compartment syndrome associated with Norovirus infection - Michael H. Liu; S. Julie-Ann Lloyd; Colin Gause; Federico Seifarth; Anthony Deross (Elsevier, 2016)
Norovirus infection is a leading cause of infectious gastroenteritis and is typically self-limited. Abdominal compartment syndrome is rare in the pediatric population. To date, there have been no reports of abdominal compartment syndrome secondary to Norovirus infection. This patient is a 7-year old female who presented with abdominal compartment syndrome and fulminant sepsis attributed to acute Norovirus infection. The patient was successfully treated with decompressive laparotomy, delayed abdominal closure, and supportive therapy. The patient's post-operative course was notable for acute hepatitis and pancreatitis, which resolved without further intervention. The patient was discharged home after a prolonged hospital stay in good condition.